Optimasi Parameter PID Pada Sistem Kontrol Suhu Alat Roasting Biji Kopi - Dewi Anggraeni; Saputra, Aditya Ilham; Sakti, Setyawan Purnomo (Jurnal Fisika Unand, 2025)
Coffee is an important commodity for Indonesia. This huge potential must be utilized optimally. One of the important stages in processing coffee beans is the process of roasting coffee beans. This research focuses on optimizing PID control parameters on coffee bean roasting equipment. The main stages in determining PID control parameters are carried out using MATLAB's PID Tuner and also the process of improving the parameter values. From this research it can be concluded that the PID parameters to improve the temperature control performance of coffee roasting equipment, in the temperature ranges of 210 °C, 215 °C, 220 °C, 225 °C, and 230 °C indicate that the PID parameters have been improved (Kp = 5, Ki = 0.017, and Kd = 2) has better performance compared to parameters obtained directly from PID Tuner Matlab (Kp = 33.4, Ki = 1, and Kd = 4.74). Parameters that have gone through the refinement process show a fairly fast rise time (123 seconds), small overshoot (2.8 °C) and no significant oscillations occur in the system. Thus, it can be concluded that the use of refined PID parameters is more optimal for controlling temperature in coffee bean roasting equipment, because it produces a better system response. By improving the PID parameter values, it is hoped that it can produce roasted coffee beans with accurate variations in maturity levels, so that users can determine the desired taste and aroma characteristics of coffee based on the maturity level.